Evaluación comparativa de tratamientos silviculturales en el crecimiento de especies forestales y características del suelo en la restauración ecológica de la cubierta forestal de la cuenca del río Jamboé, sector Numbami, Zamora Chinchipe - Jaramillo Sánchez, Leonardo Alexander (2014)
In 2011, Naturaleza y Cultura Internacional (NCI) Foundation started a process of ecological restoration in 23 ha of degraded grassland in Jamboé reservation, located in Numbami, Zamora Chinchipe. After the previously mentioned process, in 2013 an evaluation model in order to determine feasibility of the ecological restoration was implemented, comparing growth and adaptability of sown species against natural regeneration varieties. In addition, chemical analysis of soils to determine influence which occurred between the two evaluated groups and the soil chemical properties was carried out. The valuation model consisted in 5 sylvicuture treatments, distributed in 5 different types of vegetable formations. These treatments were labelled as: Pastures (T1), Pastures + Plantation (T2), Luzara (T3), Luzara + Plantation (T4) and Forest (T5), in which individuals belonging to natural regeneration larger than 50cm which their respective DAB were valuated; and, height and DAB of all sown species by ecological restoration, without counting height limit. With the obtained data, ecological parameters, periodical height increase (IPH) and diameter average periodical increase (IPD) in both observed groups were evaluated. Finally, with the chemical analysis, pH, organic matter amount occurred y essential nutrients availability of soils in each sylvicultural treatment were determined. In a six month period, natural regeneration treatments showed a mortality percentage of 5,39% and a recruitment rate of 16,42%, as well as an average height periodical increment (IPH) of 34,72cm y and a diameter average periodical increase (IPD) of 0,38cm. Concerning the treatments with sown species a mortality percentage of 24,69% and a survival percentage of 84,36% were shown. In addition, a IPH of 25,35 cm and a IPD of 0,31cm were obtained. In treatments with natural regeneration hemieliofitas species group had the best growth in height 43.52 cm, while in treatments with sown shade-intolerant species group obtained the best results with 36.11 cm. It was determined also that there is a close relationship concerning chemical properties of soils and the growth of regenerated and sown species.